ANALISIS PERBANDINGAN SIKAP KONSUMEN DALAM MEMILIH PRODUK MINYAK GORENG KEMASAN DAN CURAH (STUDI KASUS IBU RUMAH TANGGA DI KOTA PEKANBARU) - Fitriana '; Jushermi -; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine consumer attitudes on product attribute: packaging, colors, product quality, and product features and to determine whether there are differences in consumer attitudes toward in choosing branded and non branded cooking oil in Pekanbaru. The population in the study are (Household) the users branded and non branded cooking oil in Pekanbaru. The number of samples are 100 respondents by using Slovin formula and Quota sampling technique. The data analyzed by using multi attitude attribute model Fishbein and the Mann-Whitney U-test. From the results of the testing that has been done on the respondents have a positive attitude on product attribute: packaging, colors, product quality, and product features of branded and non branded cooking oil, and Mann-Whitney U-test showed that there are differences in consumer attitude on product attribute of branded and non branded cooking oil in Pekanbaru.Keywords: Product Features, Packaging, Color, QualityProducts, andConsumer Attitudes